Evaluasi penerapan standar pelayanan kefarmasian di Puskesmas - Baiq Endang Suprihartini; Nur Radiah; Muhammad Wahyu Hidayat (Universitas Mataram, 2022)
Pharmacy services is a direct service and obligation to the patients regarding the pharmacy substances with the aim to increase the public health services in the field of pharmacy. The purpose of this study is to evaluate the implementation of pharmaceutical standard at the primary health services Puskesmas. This study is conducted in descriptive research, data collection using a cross sectional survey approach. The instruments in this study was a questionnaire sourced from the Regulation of the Minister of Health No. 74 of 2016 concerning pharmaceutical service standards in Puskesmas. Respondents in this study were pharmacists at the Pagesangan Puskesmas. The management activities reach 100% of drug and medical consumables, 93.75% of equipment and supporting facilities, 100% of human resources. These results indicate that the evaluation of the implementation of pharmaceutical service standards at the Puskesmas based on pharmaceutical service indicators has been carried out well at the Pagesangan Puskesmas with an average value of 96.77%. The implementation of pharmaceutical service standards at the Pagesangan Puskesmas has met all the indicators of pharmaceutical service standards at the Puskesmas.